Management pattern and medication-related harms and its predictors in colorectal cancer patients: an institutional-based retrospective study - Kefale, Belayneh; Engidaw, Melaku Tadege; Tesfa, Desalegn; Molla, Mulugeta; Kefale, Yitayih; Tafere, Chernet (Frontiers in Oncology, 2023)
Introduction: Data on colorectal cancer (CRC) patients' thorough management practices and medication-related harms (MRH) are scarce. This study's aim was to investigate the MRHs in patients receiving CRC chemotherapy at the comprehensive specialized hospital of theMethods: A registry-based retrospective cohort study was conducted on CRC patients at the UoGCSH during 2017-2021. From February to May 2022, medical records were reviewed using a pretested data collection tool to collect socio-demographic and disease-related characteristics, MRHs, and medication regimens. MRHs occurrence and adverse drug reactions (ADRs) severity were assessed using standard guidelines and protocols. Version 16/MP of STATA for Windows was used for the analysis. Independent predictors of MRHs were investigated using logistic regression analysis. A p-value ≤0.05 was used to determine an independent variable's statistical significance.Results: One hundred forty three CRC patients were included, with a mean age of 49.9±14.5 years. About 32.9% and 33.6% had stage II and III cancer, respectively. Significant patients had co-morbidities (15.4%) and complications (13.3%). Fluorouracil (5-FU)-based regimens were given to more than half (56%) of the patients. MRHs were found in 53.1% of the patients, with a mean of 2.45±1.37 MRHs. The most common MRHs were the need for additional drug therapy, sub-therapeutic dose, DDIs, and ADRs. Being on stage IV (AOR = 27.7, 95% CI = 3.85-199.38, p = 0.001), having co-morbidity (AOR = 7.42, 95% CI = 1.80-30.59, p = 0.018) and having complication (AOR = 11.04, 95% CI = 1.72-70.95, p = 0.011) and treated with five or more drugs (AOR = 2.54, 95% CI = 1.07-6.07, p = 0.035) were independent predictors of MRHs.A fluorouracil-based treatment regimen was most frequently used. MRHs were found in nearly half of CRC patients. Furthermore, MRHs were significantly associated with cancer stage, comorbidity and complication status, and the number of medications used. Because MRHs are common, improving clinical pharmacy services is critical for optimizing drug therapy in CRC patients.